The First Experience of Dynamic Intramedullary Osteosynthesis of Diaphyseal Fractures of the Tibia Using Implants Based on Magnesium Alloy - Yatsun, Ye.V.; Ivchenko, D.V.; Holovakha, M.L. (TERRA ORTHOPAEDICA, 2020)
Summary. The efficiency of using the dynamic blocking intramedullary osteosynthesis (BIOS) technique for tibial fractures with the use of biodegradable implants based on the MS-10 magnesium alloy was determined.Objective: to approve the technique and to study the effectiveness of dynamic intramedullary osteosynthesis of diaphyseal fractures of the tibia using locking screws made of the biodegradable magnesium alloy MS-10.Materials and Methods. The study was carried out in the Department of Traumatology of the Municipal Non-Profit Enterprise “City Hospital of Emergency and Ambulance” of Zaporizhzhia City Council in Zaporizhzhia on 15 patients with diaphyseal fractures of the tibia, who underwent BIOS. Cannulated intramedullary titanium rods were used as a fixator. In the proximal section, a screw made of titanium alloy was introduced into a dynamic hole; a screw made of a biodegradable magnesium alloy MC-10 was inserted into a static hole. In the postoperative period, the patients underwent a course of complex rehabilitation measures. X-ray control was performed on day 1, at week 4, week 8, and week 16 after the surgery.Results. After the start of the dosed load on the injured limb, a fracture of the locking screw made of MC-10 alloy was radiographically recorded in all patients. The dynamic screw moves in the dynamic hole and the fracture is dynamized. The formation of callus in the fracture zone was unremarkable and took an average physiological time. The quality and structure of callus did not show any pathological features. Four months after the surgery, all patients were socially adapted and did not use additional support when moving.Conclusions. Based on the data obtained, it is possible to draw a conclusion about the possibility and advisability of using biodegradable implants made of magnesium alloy MS-10 in a dynamic BIOS of long bones of the human skeleton.